Return to work after coronary artery bypass graft surgery and investigation of its effects on patient - Ahmet Demirkol; Ayşegül Günes (BMC Public Health)
Abstract Purpose The study was conducted descriptively to examine the situations that coronary artery bypass graft surgery patients encounter during the postoperative return to work process. Methods The study reached patients who underwent coronary artery bypass graft surgery by phone between January 2021 and January 2022 at a Training and Research Hospital in Istanbul. The study universe consisted of 203 male patients under 55 who underwent surgery on the specified dates. The study was completed with 60 patients who met the inclusion criteria and could be contacted. The sociodemographic data form created by the researcher and the Return to Work Survey, which questioned CABG patients’ postoperative return to work status and related factors, were used to collect the research data. SPSS 25.0 package program was used for data analysis in the study. Continuous variables regarding the sociodemographic information of the patients were presented as mean and standard deviation, while categorical variables were presented as numbers and percentages. Results It was determined that the average time for patients to return to work after surgery was 4.10 ± 3.93 months. 16.7% (n = 10) of the patients stated that they had to switch to another job after surgery, 8.3% (n = 6) had to switch to another position in the same workplace, and 35% (n = 21) experienced physical problems such as shortness of breath, weakness, and fatigue during work. 96.7% (n = 58) of the patients stated that they received discharge training, and 88.3% (n = 53) stated that the information about work life in this training was sufficient. It was observed that the support of family members during the return to work life process was 91.7% (n = 55). Conclusion A comprehensive evaluation of the physical, mental, social, and economic conditions of individuals during the return to work life process may be beneficial in terms of revealing existing problems, facilitating factors, and completing the process healthily.